2020
DOI: 10.14407/jrpr.2020.45.3.142
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Tritium Analysis Method with High-Volume Counting Vial

Abstract: Background: Tritium (3 H) analysis in groundwater was difficult because of its low activity. Therefore, the electrolytic enrichment method was used. To improve the detection limit and for performing simple analysis, a high-volume counting vial with the available liquid scintillation counter (LSC) was investigated. Further, it was compared with a conventional 20-mL counting vial. Materials and Methods: The LSC with the electrolytic enrichment method was used 3 H analysis in groundwater. A high-volume 145-mL cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Research showed the comparison cocktail and sample volume, such as 3 H analysis in water sample using 10 mL cocktail and 10 mL water [16], 3 H analysis with the optimum ratio between cocktail and sample, namely 10:10 [17]. Mixture of 2 g sample, 6 g ultrapure water, and 12 mL scintillator [18], 1:2 ratio used for maximizing the counts [15], 3 H analysis using 8:12 ratio (sample water: AquaLight cocktail) in LSC Hidex 300 SL [19].…”
Section: Introductionmentioning
confidence: 99%
“…Research showed the comparison cocktail and sample volume, such as 3 H analysis in water sample using 10 mL cocktail and 10 mL water [16], 3 H analysis with the optimum ratio between cocktail and sample, namely 10:10 [17]. Mixture of 2 g sample, 6 g ultrapure water, and 12 mL scintillator [18], 1:2 ratio used for maximizing the counts [15], 3 H analysis using 8:12 ratio (sample water: AquaLight cocktail) in LSC Hidex 300 SL [19].…”
Section: Introductionmentioning
confidence: 99%